EFFECT OF RED MUD AND IRON ORE TAILINGS ON THE STRENGTH OF SELFCOMPACTING CONCRETE - Shetty, Kiran K.; Nayak, Gopinatha; Vijayan, Vipul (European Scientific Journal, ESJ, 2014)
The current trend all over the world is to utilize the treated and untreated industrial by-products as a raw material in concrete, which gives an eco-friendly edge to the concrete preparation process. This practice not only helps in reuse of the waste material but also creates a cleaner and greener environment.This study aims to focus on strength aspects of Self-compacting concrete (SCC) which has been prepared by partially replacing cementitiousmaterial by red mud (RM) and in the same mix, partially replacing sand by Iron Ore Tailings(IOT). Cementitious material in the SCC mixture was replaced with RM at 1%, 2%, 3% and 4%. For each RM replacement level, 10%, 20%, 30%, 40% of fine aggregate (regular sand) was replaced with IOT.